О напряженно-деформированном состоянии ортотропных толстостенных прямоугольных пластин - Григоренко, А.Я.; Бергулев, А.C.; Яремченко, C.Н. (Доповіді НАН України, 2011)
Наведено чисельно-аналітичний підхід для дослідження напружено-деформованого стану ортотропних прямокутних пластин. Задача розв'язується на основі тривимірної моделі теорії пружності. Система диференційних рівнянь в частинних похідних зводиться до одновимірної задачі з використанням методу сплайн-колокації за двома координатними напрямками. Крайова задача для системи звичайних диференційних рівнянь високого порядку розв'язується стійким чисельним методом дискретної ортогоналізації. Запропоновано приклади розрахунків для різних крайових умов. A numerically-analytical approach to researching the stress-strain state of orthotropic rectangular plates is proposed. The problem is solved on the basis of a three-dimensional model of the theory of elasticity. The system of partial differential equations is reduced to the one-dimensional problem within the method of spline-collocation in two coordinate directions. The boundary-value problem for a system of ordinary differential equations of the higher order is solved by a stable numerical method of discrete orthogonalization. The examples of calculations for various geometric parameters and boundary conditions of orthotropic rectangular plates are presented.